Strengthening collective action - Bruns, Bryan Randolph; Bruns, Pakping Chalad (International Food Policy Research Institute, 2004)
This brief reviews how citizens, nongovernmental organizations (NGOs), government agencies, and others can strengthen collective action. The authors discuss ways of facilitating collective action, of redesigning institutions and incentives and of the need for policy reform. They point out potential problems and conclude that reforms to strengthen collective action need to employ multiple approaches and to be customized by local resource users to fit their local conditions in ways that allow for continuing learning and adaptation.